Design and biological evaluation of substituted 5, 7-dihydro-6H-indolo[2, 3-c]quinolin-6-one as novel selective Haspin inhibitors. (31st December 2022) - Avula, Sreenivas; Peng, Xudan; Lang, Xingfen; Tortorella, Micky; Josselin, Béatrice; Bach, Stéphane; Bourg, Stephane; Bonnet, Pascal; Buron, Frédéric; Ruchaud, Sandrine; Routier, Sylvain; Neagoie, Cleopatra
Abstract: A library of substituted indolo[2, 3- c ]quinolone-6-ones was developed as simplified Lamellarin isosters. Synthesis was achieved from indole after a four-step pathway sequence involving iodination, a Suzuki-Miyaura cross-coupling reaction, and a reduction/lactamization sequence. The inhibitory activity of the 22 novel derivatives was assessed on Haspin kinase. Two of them possessed an IC50 of 1 and 2 nM with selectivity towards a panel of 10 other kinases including the parent kinases DYRK1A and CLK1. The most selective compound exerted additionally a very interesting cell effect on the osteosarcoma U-2 OS cell line.